Indonesian nationalism discourse on YouTube video produced by young Chinese-Indonesians - Susilo, Daniel; Sugihartati, Rahma (2021)
Access online through this link: https://www.plarideljournal.org/article/indonesian-nationalism-discourse-on-youtube-video-produced-by-young-chinese-indonesians
Keywords: YouTube (Web resource); Internet videos (Youtube); Cyberculture; Video blogs